1998
DOI: 10.1002/(sici)1096-9861(19980420)393:4<457::aid-cne5>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Spatial coding of odorant features in the glomerular layer of the rat olfactory bulb

Abstract: In order to determine whether molecular features of odorants are represented spatially in the glomerular layer of the olfactory bulb, we used metabolic mapping of [14C] 2-deoxyglucose uptake in rats exposed to equal vapor concentrations of odorants differing systematically in chemical structure. The odorants were ethyl acetate, ethyl butyrate, isoamyl acetate, and isoamyl butyrate. Statistical analysis of anatomically standardized arrays of uptake revealed that each ester produced a characteristic spatial patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
168
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(193 citation statements)
references
References 34 publications
23
168
2
Order By: Relevance
“…Because sensory axons converging on a single glomerulus outnumber principal cells by a factor of several hundred and because action potentials are predicted to consume a major part of the energy budget during signaling (48), our study raises the question of how energy is distributed to olfactory nerve axons, whatever the percentage of them is activated during odor stimulation. Studies based on 2-deoxyglucose consumption (32,33,49) clearly demonstrated that energy consumption is significant in the ONL. It is thus possible that the oxygen present in the immediate vicinity of arterioles (50) contributes to the oxygen supply of the ONL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because sensory axons converging on a single glomerulus outnumber principal cells by a factor of several hundred and because action potentials are predicted to consume a major part of the energy budget during signaling (48), our study raises the question of how energy is distributed to olfactory nerve axons, whatever the percentage of them is activated during odor stimulation. Studies based on 2-deoxyglucose consumption (32,33,49) clearly demonstrated that energy consumption is significant in the ONL. It is thus possible that the oxygen present in the immediate vicinity of arterioles (50) contributes to the oxygen supply of the ONL.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, odor stimulation reproducibly activates small glomeruli ensembles. These patterns of glomerular activation have been revealed by several methods including (i) BOLD fMRI (18)(19)(20), (ii) optical imaging of calcium (21), voltage (22), and intrinsic signals (23)(24)(25)(26)(27)(28), (iii) electrophysiological recordings (29)(30)(31), and (iv) measurements of 2-deoxyglucose consumption (32,33). Here, we use two-photon imaging to determine with a high spatial resolution the relationship between RBC flow in individual capillaries and neuronal activation.…”
mentioning
confidence: 99%
“…Imaging studies using various activity markers have shown that odor compounds evoke spatially organized, combinatorial patterns of neural activity in OBs (Mombaerts et al, 1996;Friedrich and Korsching, 1998;Johnson et al, 1998;Rubin and Katz, 1999;Belluscio and Katz, 2001;Xu et al, 2003; and ALs (Joerges et al, 1997;Carlsson et al, 2002;Hansson et al, 2003). In most of these cases, however, the cell types imaged were unknown, although in others (Zhao et al, 1998;Araneda et al, 2000;Ma and Shepherd, 2000;Gaillard et al, 2002;Wachowiak and Cohen, 2003) primary-afferent input was imaged.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical landmarks determine the origins for the radial measurements. The first section is defined by the point at which complete mitral cell and external plexiform layers can be identified (Johnson and Leon, 1996;Johnson et al, 1998Johnson et al, , 1999Schaefer et al, 2001a). The 0 -180 o axis was drawn parallel to the more ventral aspect of the subependymal layer.…”
Section: Methodsmentioning
confidence: 99%